Employee Retention Strategies to Enhance Job Satisfaction at PT Phapros Tbk Semarang - Sri Endarwati; Adhitya Yoga Prasetya (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2024)
This study investigates the employee retention strategies implemented by PT Phapros Tbk Semarang and their impact on job satisfaction, focusing on the pharmaceutical sector in Indonesia. The national pharmaceutical industry faces high turnover rates, which highlight the critical need for effective retention strategies to enhance organizational commitment and reduce employee attrition. Using a qualitative descriptive approach, this research analyzes the relationship between retention strategies and job satisfaction by collecting data through semi-structured interviews, direct observations, and document analysis. The findings indicate that PT Phapros has introduced several retention initiatives, such as competitive compensation packages, career development programs, non-financial recognition, and the use of HRIS for digital communication. The company has also embraced cultural transformation efforts to foster a supportive work environment. However, the study found that inconsistencies in the implementation of these programs across various divisions have limited their overall impact. The research concludes that a holistic, context-sensitive employee retention strategy—combining career clarity, equitable rewards, effective communication, and a supportive organizational culture—can significantly improve employee job satisfaction, motivation, and loyalty, thus contributing to the overall success and stability of the organization.